A estreita relação professor-aluno na base da experiência do ensino inspirador - Gabriela da Cunha Barbosa Saldanha (2019)
Research on problematic issues related to English teaching and learning in Brazilian regular schools have been recurrent in literature (COELHO, 2005; PAIVA, 1997; MOITA LOPES, 1996, BARCELOS, 1995; BARCELOS, 2007; MICCOLI 2010). However, according to Barcelos (2011) “what other narratives about language learning can we tell?” Narratives about motivating, inspiring experiences that allow the emergence of other similar experiences? Having this in mind, the current case study aimed at understanding inspiring experiences and practices of English teachers and students inside public school classrooms. With the purpose of knowing and reflecting about the elements that modulated inspiring learning experiences and practices, as well as the way these elements interacted resulting in the emergence of inspiring learning experiences, different research instruments were used such as a survey, with former students, questionnaire and interview with teachers nominated as inspiring by their former students and field notes from class observations. The findings from data analyses according the procedures adopted by Lamb e Wedell (2013 a), Miccoli and Lima (2012) and Lieblich, Tuval-Mashiach and Zilber (1998) – indicated the close teacher-student relationship as the key element which promotes inspiring learning experiences. A complex, dynamic and bidirectional relationship established in a macro scale of time, through moment-to-moment interactions and modulated by attitudinal, behavioral, emotional, conceptual, cultural, pedagogical, cognitive, social and contextual elements that interacted and enabled its emergence. The implications of the current study claims for the necessity of rethinking the role of social relationships, as well as of emotions in the language teacher education , so that it can be a locus of not only didactic-pedagogic development but also a locus where teachers are able to reflect over their “social emotional intelligences” (GKONOU; MERCER, 2017). In addition, this study claims for the necessity of investment in practices that promote meaningful and inspiring experiences to English students of Brazilian regular schools – through the close teacher student relationship – so that the inefficiency paradigm of English learning in this context can be deconstructed.